A meta-regression analysis on judicial efficiency literature: The role of methodological and courts diversity - Francesco Aiello; Graziella Bonanno; Francesco Foglia (Journal of Applied Economics, 2024)
This study presents a meta-regression analysis on the literature of courts efficiency. The metadata set comprises 264 efficiency scores retrieved from 36 papers published from 1992 to 2019. Our models explain a substantial proportion of both within- and between-study heterogeneity. Estimates indicate that the efficiency score of primary papers decreases when the sample size and the sum of inputs and outputs increase. It is also found that parametric papers yield higher efficiency scores than non-parametric studies. Furthermore, the scores obtained in studies that analyse first-instance courts are significantly higher than those from studies on appeal courts. Finally, papers focusing on specific courts (tax, civil or criminal) yield efficiency scores that are higher than those obtained in studies where the analysed courts are mixed.
Keywords: 330; Courts; frontier models; judicial system; meta-analysis